Promising photoluminescence optical approach for triiodothyronine hormone determination based on smart copper metal–organic framework nanoparticles. (19th June 2019) - Sheta, Sheta M.; El‐Sheikh, Said M.; Abd‐Elzaher, Mohkles M.
Abstract : A copper metal–organic framework nanoparticles (Cu‐MOF‐NPs) synthesized via simple technique. The prepared Cu‐MOF‐NPs nanoparticles were further characterized using 1 H‐NMR, FE‐SEM/EDX and thermal study (DSC/TGA). The FE‐SEM/EDX, thermal analysis, and NMR spectrum data with the other analysis support the nano‐Cu‐MOF structure and the monomeric unit (n[Cu (AIP)2 (APY)(H2 O)2 ].4H2 O) of Cu‐MOF‐NPs. The photoluminescence (PL) studies of triiodothyronine hormone (T3) based on the prepared Cu‐MOF‐NPs investigated. The results revealed that the Cu‐MOF‐NPs might be used as a biosensor in the determination of triiodothyronine hormone (T3) in biological fluids through a significant quenching of the photoluminescence intensity of Cu‐MOF‐NPs at excitation wavelength 492 nm. The calibration plot achieved over the concentration range 0.0–200.0 ng/dL T3 hormone with a correlation coefficient 0.996 and limit of detection (LOD) and quantification (LOQ) 0.198 and 0.60 ng/dL, respectively. The PL spectra are indicating that Cu‐MOF‐NPs has highly selective sensing properties for T3 hormone without interfering with other human many hormones types. This approach considered a promising analytical tool for early diagnosis of the cases of thyroid disease. The mechanism of quenching between the Cu‐MOF‐NPs, and T3 hormone studied. The mechanism was a dynamic type and obtained due to the energy transfer mechanism. Abstract : For the first time a promising photoluminescence approach for T3 hormone determination based on Cu‐MOF‐NPs. This approach could be promising analytical tool for early diagnosis of the cases thyroid disease. The proposed approach offered many advantages, wide concentration range 0.0‐200.0 ng/dL, a lower LOD=0.198 ng/dL and LOQ=0.60 ng/dL than other published reports. Cu‐MOF‐NPs has a selectivity and sensitivity for T3 hormone without interfering with other hormones. The mechanism of quenching between the Cu‐MOF‐NPs and T3 hormone was dynamic type. HIGHLIGHTS: For the first time a promising photoluminescence approach to determine T3 hormone based on MOF A promising analytical tool for early diagnosis of the cases thyroid disease The proposed approach offered many advantages compared to published methods Cu‐MOF‐NPs has a selectivity and sensitivity for T3 hormone without interfering other hormones The mechanism of quenching between the Cu‐MOF‐NPs and T3 hormone was well studied.